Targeted Preoperative Autologous Blood Donation in Total Knee Arthroplasty Reduces the Need for Postoperative Transfusion - Bou Monsef, Jad (Springer US, 2013)
BACKGROUND: Preoperative donation of autologous blood has been widely used to minimize the potential risk of allogeneic transfusions in total knee arthroplasty. A previous study from our center revealed that preoperative autologous donation reduces the allogeneic blood exposure for anemic patients but has no effect for non-anemic patients. QUESTIONS/PURPOSES: The current study investigates the impact of a targeted blood donation protocol on overall transfusion rates and the incidence of allogeneic blood transfusions. METHODS: Prospectively, 372 patients undergoing 425 unilateral primary knee replacements were preoperatively screened by the Blood Preservation Center between 2009 and 2012. Anemic patients with a hemoglobin level less than 13.5 g/dL were advised to donate blood, while non-anemic patients did not donate. RESULTS: Non-anemic patients who did not donate blood required allogeneic blood transfusions in 5.9% of the patients. The overall rate of allogeneic transfusion was significantly lower for anemic patients who donated autologous blood (group A, 9%) than those who did not donate (group B, 33%; p < 0.001). Donating autologous blood did increase the overall transfusion rate of anemic patients to 0.84 per patient in group A compared to 0.41 per patient in group B (p < 0.001). CONCLUSION: This investigation confirms that abandoning preoperative autologous blood donation for non-anemic patients does not increase allogeneic blood transfusion rates but significantly lowers overall transfusion rates. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11420-013-9346-8) contains supplementary material, which is available to authorized users.